(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The following text concerns "The infernal hunt" contained in the Decameron (novel VIII, journey V) by Boccaccio (no date). The levels of narrative were verified - going from the tale (within which a theatrical spectacle occurs) to the Boticelli painting bearing the same title. Going from one narrative plane to the other, issues concerning sin circulate, as seen from the masculine and feminine points of view. The gender "morality" has its meaning amplified in a variety of comical keys and relative to satire, caricature and parody. Highlighted is the masculine power which imposes itself, even in the conditions in which actions are condemned by the institution of the Church. What is left for women is to abide by the pedagogy of "virtue".